The Effect of Application of Nurse Therapeutic Communication on Cooperative Behavior of Patients with Mental Disorders - Risna Risna; Neila Fauzia (Budapest International Research and Critics University, 2021)
Therapeutic communication is one of the tools in carrying out the nursing process, where through communication carried out by nurses consciously, directed, and has a goal, namely to heal patients. Mental disorders are clinically significant syndromes or behavioral patterns associated with distress or suffering and may interfere with one or more functions of human life. The purpose of this study was to determine the effect of the application of nurse therapeutic communication on cooperative behavior of mental patients in the mental room of RSUD Tgk. Chik at Tiro Sigli. The research design was a pre-experimental design, with a one group pre and post test design, to obtain cooperative behavior before and after the application of therapeutic communication. This type of research is a quasi-experimental design with a one-group pre-test and post-test design with a sample of 52 respondents. Statistical test using Wilcoxon Signed Range Test. The results showed that there was an effect of therapeutic communication on patient cooperative behavior such as self-care abilities (eating, bathing and elimination) with a p value of 0.000. It is expected that nurses can pay more attention to the therapeutic communication process in patients, especially those who experience self-care deficits according to the nursing action plan and on an ongoing basis.